2023
DOI: 10.1007/s40122-023-00509-x
|View full text |Cite
|
Sign up to set email alerts
|

Letter to the Editor Regarding “Effect of Transcutaneous Electrical Acupoint Stimulation Combined with Transversus Abdominis Plane Block on Postoperative Recovery in Elderly Patients Undergoing Laparoscopic Gastric Cancer Surgery: A Randomized Controlled Trial”

Abstract: Re: Xing R, et al. Effect of transcutaneous electrical acupoint stimulation combined with transversus abdominis plane block on postoperative recovery in elderly patients undergoing laparoscopic gastric cancer surgery: a randomized controlled trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…[ 49 ] Notably, it has been also shown that the proportion of patients reporting chronic thoracic pain at 3 months post-surgery is significantly higher in patients treated intraoperatively with RF compared to patients treated with fentanyl. [ 50 ] Patients referred pain mostly around the site of incision in both groups. However, there were no differences in pain perception between the two groups at 6- and 12-months following surgery, being the last the primary endpoint of the study.…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 49 ] Notably, it has been also shown that the proportion of patients reporting chronic thoracic pain at 3 months post-surgery is significantly higher in patients treated intraoperatively with RF compared to patients treated with fentanyl. [ 50 ] Patients referred pain mostly around the site of incision in both groups. However, there were no differences in pain perception between the two groups at 6- and 12-months following surgery, being the last the primary endpoint of the study.…”
Section: Literature Searchmentioning
confidence: 99%
“…At 3 months, a dose-related effect of RF on pain was observed, with OR of 1.3 (95% 0.5 to 3.1) and 3.3 (95% CI 1.4 to 8.1) for a cumulative dose of <1.875 mcg and ≥1.875 mcg, respectively. [ 50 ]…”
Section: Literature Searchmentioning
confidence: 99%